Clinical implications of plasma circulating tumor DNA in gynecologic cancer patients. Issue 1 (17th September 2020) - Charo, Lindsey M.; Eskander, Ramez N.; Okamura, Ryosuke; Patel, Sandip P.; Nikanjam, Mina; Lanman, Richard B.; Piccioni, David E.; Kato, Shumei; McHale, Michael T.; Kurzrock, Razelle
Abstract : Molecular characterization of cancers is important in dictating prognostic factors and directing therapy. Next‐generation sequencing of plasma circulating tumor DNA (ctDNA) offers less invasive, more convenient collection, and a more real‐time representation of a tumor and its molecular heterogeneity than tissue. However, little is known about the clinical implications of ctDNA assessment in gynecologic cancer. We describe the molecular landscape identified on ctDNA, ctDNA concordance with tissue‐based analysis, and factors associated with overall survival (OS) in gynecologic cancer patients with ctDNA analysis. We reviewed clinicopathologic and genomic information for 105 consecutive gynecologic cancer patients with ctDNA analysis, including 78 with tissue‐based sequencing, enrolled in the Profile‐Related Evidence Determining Individualized Cancer Therapy (NCT02478931) trial at the University of California San Diego Moores Cancer Center starting July 2014. Tumors included ovarian (47.6%), uterine (35.2%), cervical (12.4%), vulvovaginal (2.9%), and unknown gynecologic primary (1.9%). Most ovarian and uterine cancers (86%) were high grade. 34% ( N  = 17) of ovarian cancers had BRCA alterations, and 22% ( N  = 11) were platinum sensitive. Patients received median 2 (range 0–13) lines of therapy prior to ctDNA collection. Most (75.2%) had at least one characterized alteration on ctDNA analysis, and the majority had unique genomic profiles on ctDNA. Most common alterations were TP53 ( N  = 59, 56.2% of patients), PIK3CA ( N  = 26, 24.8%), KRAS ( N  = 14, 13.3%), BRAF ( N  = 10, 9.5%), ERBB2 ( N  = 8, 7.6%), and MYC ( N  = 8, 7.6%). Higher ctDNA maximum mutation allele frequency was associated with worse OS [hazard ratio (HR): 1.91, P  = 0.03], while therapy matched to ctDNA alterations ( N  = 33 patients) was independently associated with improved OS (HR: 0.34, P  = 0.007) compared to unmatched therapy ( N  = 28 patients) in multivariate analysis. Tissue and ctDNA genomic results showed high concordance unaffected by temporal or spatial factors. This study provides evidence for the utility of ctDNA in determining outcome and individualizing cancer therapy in patients with gynecologic cancer. Abstract : In gynecologic cancer patients, therapy matched to ctDNA alterations ( N  = 33 patients) was independently associated with improved overall survival (hazard ratio: 0.34, P  = 0.007) compared to unmatched therapy ( N  = 28 patients) in multivariate analysis. Tissue and ctDNA genomic results showed high concordance unaffected by temporal or spatial factors. ctDNA may be an important tool to individualize cancer therapy in patients with gynecologic cancer.